Metaphora conectens, argumentative metaphor, transferential function, and rhetorical-cultural code (Castilla. Estudios de Literatura, 2026)
This article deals with metaphor and its function as a communicative link between the producer and the receiver, including contextual connections. It studies the metaphora conectens as a metaphor with great connecting power due to its cultural basis. It examines the configuration of the rhetorical-cultural code that is closely linked to this connection and focuses on the argumentative function of the metaphora conectens in both rhetorical discourse and literary works. Several cases of the impact of this type of metaphor are studied in light of its perlocutionary implication of argumentative function. The article is a contribution to transferential theory and criticism.
Keywords: metaphor; transfer; argumentation; rhetorical-cultural code; transferential theory and criticism